2020
DOI: 10.22271/chemi.2020.v8.i3e.9242
|View full text |Cite
|
Sign up to set email alerts
|

Value addition and storage study of khakhra fortification with garden cress seed (Lepidium sativum)

Abstract: Khakhra is a popular vegetarian roasted 'Gujarati' Indian thin cracker bread or snack item made from whole-wheat flour and oil. In present investigation efforts were made to prepare khakhra by using different proportions and variety of flours i.e. S0, S1, S2, S3, and S4. The study was carried out to find out the development of value added khakhra by using different levels of flours whole-wheat flour, garden cress seed and buckwheat flour. The khakhra was prepared by wheat flour with substituting garden cress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Further, kodo masala khakhras stored in silver pouch showed significant increase of 4.11 to 4.86% (0 day to 60 th day) and kodo masala khakhras stored in plastic pouch showed significant increase from 4.14 to 5.02% (0 day to 60 th day). Similar findings were observed by Solanke G.M et al, 2020 [23] and authors reported that increase in moisture content during storage period is because of hygroscopic nature of whole wheat flour and other factors such as temperature, relative humidity present in air. 6 shows the organoleptic scores of masala khakhra on storage.…”
Section: Discussionsupporting
confidence: 88%
“…Further, kodo masala khakhras stored in silver pouch showed significant increase of 4.11 to 4.86% (0 day to 60 th day) and kodo masala khakhras stored in plastic pouch showed significant increase from 4.14 to 5.02% (0 day to 60 th day). Similar findings were observed by Solanke G.M et al, 2020 [23] and authors reported that increase in moisture content during storage period is because of hygroscopic nature of whole wheat flour and other factors such as temperature, relative humidity present in air. 6 shows the organoleptic scores of masala khakhra on storage.…”
Section: Discussionsupporting
confidence: 88%